2021
DOI: 10.1186/s12886-021-01891-w
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between education levels, lifestyle, and religion regarding the prevalence of myopia in Israel

Abstract: Background The ultra-Orthodox Jewish community has a unique lifestyle including minimal outdoor activity and intense, prolonged nearby work, beginning at a very young age. Their prevalence of myopia is extremely high. This paper provides a unique insight into the attitudes of this community towards myopia. Methods Ultra-Orthodox Jewish parents of children who came to the pediatric ophthalmology clinic in one tertiary care and two community centers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Of these, two studies [ 36 , 52 ] used cycloplegic refraction, which is thought to more accurately estimate the prevalence of myopia [ 59 ]. The lower prevalence of myopia in Africa compared with the other regions may be related to the differences in genetic predisposition to myopia development, and to culture [ 60 62 ]. Although the role of genetics in the development and progression of myopia is reported to be small [ 12 ], it is believed to have a role in an individual’s susceptibility to environmental risk factors for myopia [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, two studies [ 36 , 52 ] used cycloplegic refraction, which is thought to more accurately estimate the prevalence of myopia [ 59 ]. The lower prevalence of myopia in Africa compared with the other regions may be related to the differences in genetic predisposition to myopia development, and to culture [ 60 62 ]. Although the role of genetics in the development and progression of myopia is reported to be small [ 12 ], it is believed to have a role in an individual’s susceptibility to environmental risk factors for myopia [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In areas with high prevalence of myopia such as Asian countries, prevention is an urgent task. A variety of studies investigated lifestyle (mainly including outdoor, near work, and screen use) [51][52][53][54] , but how these factors work together and lead to myopia or promote myopia progression is intricated. Though many efforts have been tried to reduce the incidence of myopia and the effect of myopia prevention was checked 55 , most of them implemented only a few intervention measures which may not be suitable for every single person in practice.…”
Section: Discussionmentioning
confidence: 99%
“…This is because we specifically selected studies that defined myopia as a spherical equivalent of ≤−0.5 D. The relatively low prevalence of myopia observed in LATAM children and adolescents aligns with the findings from other studies, indicating a lower prevalence of myopia in Western children than in Asian children [ 8 , 47 ]. Numerous studies have demonstrated the significant influence of environmental factors on myopia development, particularly near-work activities, such as writing, reading, and computer use [ 48 - 50 ]. In many LATAM countries, there is a difference in the age at which children begin formal education compared with other Asian countries.…”
Section: Reviewmentioning
confidence: 99%